Tribological Analysis Of A 3D-Printed Internal Triangular Flip ABS Pin During Running-In Stage - Abdullah, Muhammad Ilman Hakimi Chua; Mohamad Norani, Mohamad Nordin; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; Ramli, Faiz Redza; Tamaldin, Noreffendy (Malaysian Tribology Society, 2020)
The objective of this study was to investigate the correlation between the coefficient of friction (COF) and the running-in distance as well as the wear properties of acrylonitrile butadiene styrene (ABS) polymer. This was achieved by comparing a 3D-printed internal triangular flip ABS pin with a 3D-printed solid ABS pin under varying loads and sliding speeds. The ABS pin that was investigated was modified into a triangular flip internal structure and manufactured via 3D printing through fused filament fabrication (FFF). The experiment was conducted under dry conditions using a pin-on-disc tribometer. At a load of 58.68 N and sliding speed of 600 rpm, the runningin distance of 145.16 m showed that the triangular flip ABS pin produced a lower steady-state COF (0.305) compared to the solid ABS pin. The triangular flip ABS pin exhibited the effects of an early contact microstructure as well as changes in the surface area composition that resulted in a low maximum stress, thereby decreasing the COF. A morphological analysis using scanning electron microscopy (SEM) revealed that delamination and abrasion were the main mechanisms of wear